An Adieu to Europe: Impossible Necessity of Balkans Politics: Едно збогум на Европа: Невозможната неопходност на балканската политика - Blagojević, Jelisaveta; Čemerski, Ognen (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): Jelisaveta Blagojević | Јелисавета Благојевиќ Title (English): An Adieu to Europe: Impossible Necessity of Balkans Politics Title (Macedonian): Едно збогум на Европа: Невозможната неопходност на балканската политика Translated by (English to Macedonian): Ognen Čemerski | Огнен Чемерски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 99-114 Page Count: 16 Citation (English): Jelisaveta Blagojević, “An Adieu to Europe: Impossible Necessity of Balkans Politics,” Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 99-114. Citation (Macedonian): Јелисавета Благојевиќ, „Едно збогум на Европа: Невозможната неопходност на балканската политика“, превод од англиски Огнен Чемерски, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 99-114.